Quantitative Trait Locus Analysis of Protein and Oil Content in Response to Planting Density in Soybean (Glycine max [L.] Merri.) Seeds Based on SNP Linkage Mapping - Tian, Xiaocui; Zhang, Kaixin; Liu, Shulin; Sun, Xu; Li, Xiyu; Song, Jie; Qi, Zhongying; Wang, Yue; Fang, Yanlong; Wang, Jiajing; Jiang, Sitong; Yang, Chang; et al. (Frontiers in Genetics, 2020)
Breeding varieties suitable to high plant densities is of importance and protein and oil content in soybean seed accounted for the value of this crop, it is especially important to explore the genetic basement on response of varieties genotype to planting density. In this study, mapping QTL (quantitative trait loci) for protein and oil content of FW-RILs (four-way recombinant inbred lines) population was performed based on an SNP (single nucleotide polymorphism) linkage map, using inclusive composite interval mapping. A total of 21 QTLs for protein content and 32 for oil content were identified in planting density 22.5×105 plant/ha (D1), 21 QTLs for protein and 21 for oil content were identified in planting density 30×105 plant/ha (D2), respectively. Among all detected QTL, one PC QTL was identified under two densities. In addition, 49 QTLs for response to density of protein content and oil content were identified. Of all QTLs, 112 QTLs are agreement with previous reports, 31 were newly identified. 32 QTLs could each explain more than 10% of the phenotypic variation for the corresponding trait，which we based on 16 QTL of marker interval distance around 1Mb were detected under different densities and density response, pathway analysis identified five protein candidate genes that are may be involved in protein synthesis metabolism. These results help to increase our understanding for protein and oil content synthesis metabolic mechanism, simultaneously, contribute to enhance protein and oil content in soybean, increased soybean yield.